Organisational Commitment on the Job Performance of Employees in An International Bank - Lim, Vi Vien (2015)
This research explores the multifaceted nature of commitment among the employees working in a ast-pace,highly competitive organisation – an international global leader in the banking industry, operating locally in Malaysia. Being a foreign bank in Malaysia during the aftermath of the recent global financial crisis presents many challenges, especially competition against strong local banks and rising customer demands. To remain as a top player, the bank must continuously improve their performance by either increasing business revenues or reducing operational cost. This leads to resource-based theory where human capital is the vital asset through which the organisation attains competitive advantage. It is this focus on human capital that brings about the study on psychological and behavioural elements. The aim of this study is to discover the influence of organisational commitment towards job performance through measurement of employee’s willingness to perform. Organisational commitment as a three-dimensional concept postulated by Meyer and Allen (1991) is to be tested in this study to analyse the impact of organisational commitment towards employee job performance. In addition, the researcher also attempts to identify the prevalent culture and its influence on organisational commitment and employee job performance within the organisation as experts and academics are starting to recognise the importance of organisational culture. Existing literature on the relevant subject matter was consulted and referenced in order to derive the conceptual framework used in this study. Data was gathered through a quantitative approach. A total of 210 employees of the bank participated in the survey questionnaire which also allowed for open ended feedback. The results were then statistically analysed. Findings confirm that organisational commitment does indeed have a significant, positive correlation towards job performance. Of the three components of commitment, affective commitment contributed the highest correlation towards job performance, followed closely by normative commitment and lastly continuance commitment. The organisational culture within the bank was perceived as being generally bureaucratic, thus hinting at a possible strategy on the part of the bank as findings show that the relationship between organisational commitment and job performance was also the strongest from employees who perceived the culture as bureaucratic. Further analyses were then performed through segmentation of respondent demographics. The implications of the findings were then used to recommend possible strategies for the bank to consider and action upon. Few key recommendations on building a high commitment organisation are selective hiring and staffing, performance based recognition and rewards,peer-to-peer recognition and elite leadership programs for high performers. This is also achieved through developing a high performance synergy culture that is only unique to the bank.